Autoimmunity in Pulmonary Arterial Hypertension: Evidence for Local Immunoglobulin Production - Shu, Ting; Xing, Yanjiang; Wang, Jing (Frontiers in Cardiovascular Medicine, 2021)
Pulmonary arterial hypertension (PAH) is a progressive life-threating disease. The notion that autoimmunity is associated with PAH is widely recognized by the observations that patients with connective tissue diseases or virus infection are more susceptible to PAH. However, growing evidence supports that idiopathic PAH (IPAH) patients with no autoimmune diseases also have auto-antibodies. Anti-inflammation therapy shows less help in decreasing auto-antibodies, therefore, elucidating the process of immunoglobulins production is in great need. Maladaptive immune response in lung tissues is considered implicating in the local auto-antibodies production in IPAH patients. In this review, we will discuss the specific cell types involved in lung in situ immune response, the potential auto-antigens and the contribution of local immunoglobulin production in PAH development, providing a theoretical basis for drug development and precise treatment in PAH patients.